The effect of systemic corticosteroids on the innate and adaptive immune system in children with steroid responsive nephrotic syndrome - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ALPAY, HARİKA; BARIŞ, HATİCE EZGİ; GÖKCE, İBRAHİM; ÖĞÜLÜR, İSMAİL; YILDIZ, NURDAN; BARIŞ, SAFA (SPRINGER, 2016)
The severity and duration of immunosuppression caused by corticosteroids (CSs) usage have not been extensively studied. We aimed to investigate the effects of CSs on the various compartments of immune system in relation to timing of initiation and persistence of therapy. Pediatric patients with idiopathic nephrotic syndrome (NS) treated with 2 mg/kg/day prednisolone and healthy control (HC) were enrolled. Blood samples were drawn for immunologic analyses at baseline and at the first and second weeks and first, second, and third months of CS therapy in addition to first and second weeks and first, second, and third months of discontinuation. Fourteen patients (M/F, 7/7) between 1 and 8 years old were evaluated. Untreated NS exhibited high absolute lymphocyte count (ALC)(p = 0.010), absolute CD3(+) T cells (p = 0.020) and absolute CD8(+) T cells (p = 0.006) compared to HC. Suppression in ALC was observed and nadir value was noted at first month of therapy compared to baseline (p = 0.002). The CD4(+) (p = 0.036) and CD8(+) T cell (p = 0.013) counts decreased significantly at the first week of treatment compared to baseline. While baseline B cell counts was indifferent from HC, gradually increased in 2 weeks of CS initiation and decreased during the treatment with a statistical significance compared to HC (p = 0.010). However, after cessation of CS, B cell counts continued to decline and found to be significantly different than baseline at first week (p = 0.008) and at third month (p = 0.040). Conclusion: Apart from baseline lymphocyte subset changing observed in untreated NS patients, our data implies that T cells were suppressed very early in the CS treatment. Interestingly, depressed B cell counts were detected later but persisted even after CS cessation. Due to early decrease in T cells, it would be beneficial to assume the patients as immunosuppressed at the very beginning of CS treatment to avoid infections.
Keywords: Corticosteroids; Nephrotic syndrome; Children; Lymphocytes; Neutrophils; Immunosuppression; LYMPHOCYTE SUBSETS; T-CELLS; THERAPY; GLUCOCORTICOIDS; PATHOGENESIS; APOPTOSIS; LUPUS